Drought-Stress Tolerance in Wheat Seedlings Conferred by Phenazine-Producing Rhizobacteria - Mahmoudi, Tessa Rose; Yu, Jun Myoung; Liu, Shuyu; Pierson, Leland S.; Pierson, Elizabeth A. (Frontiers in Microbiology, 2019)
The specific role of phenazines produced by rhizosphere-colonizing Pseudomonas in mediating wheat seedling drought-stress tolerance and recovery from water deficit was investigated using Pseudomonas chlororaphis 30-84 and isogenic derivatives deficient or enhanced in phenazine production compared to wild type. Following a 7-day water deficit, seedlings that received no-inoculum or were colonized by the phenazine mutant wilted to collapse, whereas seedlings colonized by phenazine producers displayed less severe symptoms. After a 7-day recovery period, survival of seedlings colonized by phenazine-producing strains exceeded 80%, but was less than 60% for no-inoculum controls. A second 7-day water deficit reduced overall survival rates to less than 10% for no-inoculum control seedlings, whereas survival was ~50% for seedlings colonized by phenazine-producers. The relative water content of seedlings colonized by phenazine-producers was 10-20% greater than for the no-inoculum controls at every stage of water deficit and recovery, resulting in higher recovery indices than observed for the no-inoculum controls. For 10-day water deficits causing the collapse of all seedlings, survival rates remained high for plants colonized by phenazine-producers, especially the enhanced phenazine producer (~74%), relative to the no-inoculum control (~25%). These observations indicate that seedlings colonized by the phenazine-producing strains suffered less from dehydration during water deficit and recovered better, potentially contributing to better resilience from a second drought/recovery cycle. Seedlings colonized by phenazine-producing strains invested more in root system and produced 1.5 to 2 fold more root tips than seedlings colonized by the phenazine mutant or the no-inoculum controls when grown with or without water deficit. The results suggest that the presence of phenazine-producing bacteria in the rhizosphere provides wheat seedlings with a longer adjustment period resulting in greater drought-stress avoidance and resilience.